KORELASI ANTARA BRACHIAL-ANKLE PULSE WAVE VELOCITY DAN PROFIL LIPID PADA PASIEN DIABETES GERIATRIK - Ratna Saraswati, Made; Suka Aryana, IGP; Astika, Nym; Kuswardani, Tuty; Suastika, K (journal of internal medicine, 2012)
Brachial-ankle pulse wave velocity (baPWV) is an indicator of limb arterial stiffness. Dislipidemia is a major risk factor of atherosclerosis and may worsen baPWV by increasing the blood viscosity. This study aims to know the correlation between baPWV and the lipid profile in diabetic geriatric patients. Cross sectional analytic study has conducted in geriatric polyclinic, Sanglah hospital. Pulse wave velocity was measured using an automatic device (Fukuda VS 1000). Lipid profile were taken before test was done. Data was expressed in mean + SD, analyzed by t-test compare mean and Pearson correlation by using SPSS 11.0. There were 61 patients involved, 40 (65.6%) male and 21 (34.4%) female, age between 60-82 (mean 67.23 + 5.79) years old. Cholesterol total level, LDL-C, HDL-C, and triglyceride were vary among subject, range (means + SD) as 96-312 (198.7 + 42.3) mg/dL, 54-314 (133.2 + 40.4) mg/dL, 27-67 (45,5 + 9.0) mg/dL, and 51-438 (138.6 + 80.0) mg/dL, respectively. BaPWV on the right limbs were between 920-2260 (1605.4 + 228.5) cm/sec, on the left limbs were 870-2240 (1628.0 + 274.8) cm/sec, and mean right/left limbs baPWV were 895-2240 (1616.7 + 241.8) cm/sec. A significant correlation were found between triglyceride level and the left baPWV (r = 0.3, p = 0.019), while no significant correlation were found on the right side and mean r/l. There were significant difference of left limb baPWV among high (>150 mg/dL) and normal triglyceride level group (<150 mg/dL, according ATP-III). Brachial-ankle pulse wave velocity correlated positively with triglyceride level in diabetic geriatric patients.
Keywords: Brachial-ankle Pulse Wave Velocity (baPWV), lipid profile, diabetic geriatric